1973
DOI: 10.1038/bjc.1973.165
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Carcinoma of the Large Bowel in Man Following Transplantation into Immune Deprived Mice

Abstract: Summary.-The growth of carcinoma of the human large bowel was studied in the first 2 passages in immune deprived mice. The tumours were obtained from large bowel resections on 3 people. There was a strong histological similarity between the patient's tumour and the tumour that grew subcutaneously in the mice 2-8 months after implantation. One dissimilarity observed was a higher mitotic index in some of the tumours growing in the immune deprived animals. In the second passage of the bowel tumours, cells were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…In this tumour series, Line BR, although moderately well differentiated, histologically resembled the more poorly differentiated areas of the human primary tumour. Similar observations were made by Cobb (1973) in one tumour line, and Povlsen and Rygaard (1971) found that a poorly differentiated human colonic tumour assumed an anaplastic appearance upon implantation into nude mice. It is possible that this apparent selection was caused by the implantation of non-representative areas of the human primary tumour.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this tumour series, Line BR, although moderately well differentiated, histologically resembled the more poorly differentiated areas of the human primary tumour. Similar observations were made by Cobb (1973) in one tumour line, and Povlsen and Rygaard (1971) found that a poorly differentiated human colonic tumour assumed an anaplastic appearance upon implantation into nude mice. It is possible that this apparent selection was caused by the implantation of non-representative areas of the human primary tumour.…”
Section: Discussionsupporting
confidence: 78%
“…THERE have been many reports in the literature on the successful growth and maintenance of human colorectal tumours in immune-deprived mice (Houghton and Taylor, 1976;Cobb, 1973; Pickard, Cobb and Steel, 1975) and in nude mice (Povlsen and Rygaard, 1971). Some data regarding the chemosensitivity of human colorectal tumour xenografts are now available (Houghton, Houghton and Taylor, 1977;Kopper and Steel, 1975;Cobb and Mitchley, 1974).…”
mentioning
confidence: 99%
“…THE development of xenografting techniques, enabling human tumours to be grown in immune-suppressed mice (as shown for example by Castro, 1972, andCobb, 1973), has made it possible to experiment in the laboratory on tumours of human origin, and to study the effect on them of the cytotoxic agents used in cancer therapy.…”
mentioning
confidence: 99%
“…Six additional samples of tumour tissue were obtained surgically from a transplantable human colonic carcinoma growing in immune deprived mice (Cobb, 1973) and used for studies immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the establishment of the tumour cell cultures proved rather difficult, although some long-term (7 month) survivals were achieved. This contrasts with the ready transplantation of primary human colorectal carcinomata into suitably immunologically deprived experimental animals (Cobb, 1973;Detre and Gazet, 1973). Utilizing this latter procedure and harvesting cells from such tumours did not yield cell preparations from which cells grew or were maintained more readily.…”
Section: Organ Culturesmentioning
confidence: 98%